Intrinsic Molybdenum‐Based POMOFs with Impressive Gas Adsorptions and Photochromism - Deng, Lan; Dong, Xin; Zhou, Zhao‐Hui (Chemistry : a European journal, 2021)
Novel molybdenum(VI/V) POM‐based self‐constructed frameworks [MoVI12O24(μ2‐O)12(trz)6(H2O)6] ⋅ 6Hma ⋅ 18H2O (1, Htrz=1H‐1,2,3‐triazole, ma=methylamine), [MoVI7O14(μ2‐O)8(trz)5(H2O)] ⋅ 7Hma ⋅ 5H2O (2), Na3[MoV6O6(μ2‐O)9(Htrz)3(trz)3] ⋅ 7.5H2O (3) and [MoV8O8(μ2‐O)12(Htrz)8] ⋅ 30H2O (4) have been covalently decorated with tri‐coordinated deprotonated/protonated 1,2,3‐triazoles. Channels with an inner diameter of 7.5 Å were found in 1, whereas a tunnel composed of stacking molecules with an inner diameter of 4.1 Å along the b‐axis exists in 2; it is occupied by free disordered methylamines, showing selective adsorption of O2 and CO2 at 25 °C. Obvious downfield shifts were observed by 13C NMR spectroscopies for methylamines inside the confined channels in 1 and 2. There are diversified pores in 3 and 4, which are formed by the molecules themselves and intermolecular accumulations. Adsorption tests indicate that 3 and 4 are fine adsorption materials for CH4 and CO2 under low pressure that rely on the environments built by the POMs. Correspondingly, 1 and 2 display reversible photoresponsive thermochromism that is subtlety influenced by the channels. The polyoxometalate organic frameworks (POMOFs) with multiple functional adsorptions are easy to assemble. Their photo‐/thermoresponse properties offer a new pathway for the self‐constructions of one‐off hybrid materials that possess the good properties of both POMs and MOFs. Best of both worlds: Novel intrinsic polyoxometalate (POM)‐based microporous frameworks with 1H‐1,2,3‐triazoles as auxiliary agents possess an impressive interrelated nature derived from both POM and MOFs, for example, excellent adsorption affinities for common gases like CO2, O2 and CH4 as well as admirable photochromic properties.